Quasi-Stationary States in Ionic Liquid-Liquid Crystal Mixtures at the Nematic-Isotropic Phase Transition - Datta, Alokmay; Yoshikawa, Kenichi; Yoshida, Yukihiro; Saito, Gunzi (Frontiers in Physics, 2020)
An open system is a system driven away from equilibrium by a source that supplies an inflow of energy and a sink to maintain an outflow. A typical example of an open system is a system close to its phase transition temperature under irradiation by a laser. This provides a steady flow of energy through a photon flux. The sink in that case is the environment to which energy is lost in the form of heat dissipation. Creation of such a thermodynamically open state suggests that we can expect generation of exotic spatio-temporal structures length-scale independent correlation maintained under the global dissipative forces provided by the surroundings. Internal long-range forces can bring in additional spatio-temporal correlations, giving rise to states with a very long lifetime, the ‘quasistationary states’ (QSS). In this communication, we report evolution of quasistationary states, in a mixture of the well-known liquid crystal (N-(4-methoxybenzylidene)-4-butylaniline, MBBA) and an iron-based room temperature ionic liquid (RTIL), namely, 1-ethyl-3-methylimidazolium tetrachloroferrate (EMIF) at the Nematic-Isotropic phase transition, when focused radiation with 532 nm wavelength from a Nd:YAG laser (200-300 mW optical power) is incident on the sample. We explain the QSS by invoking a sharp negative thermal gradient due to the laser photon flux and dipolar interactions. In our model, the dipoles are the charge transfer complexes (CTCs) formed in the RTIL by resonant laser pumping, which create an orientational ordering and balance the fluctuating force of the thermal gradient to create the QSS. In the absence of such CTCs in a mixture of MBBA and a Gallium-based RTIL (1-ethyl-3-methylimidazolium tetrachlorogallate, EMIG), the QSS was not observed.